(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses one of the great values of the Uzbek people, which has been preserved from ancient times to the present day and has never lost its significance, namely, the high level of respect for parents and the influence of literature and language on the development of the spirituality of the family.